Worries of open source projects' contributors: Patterns, structures and engagement implications. - Poba-Nzaou, Placide; Uwizeyemungu, Sylvestre (Computers in Human Behavior, 2019)
Several organizations depend on open source software (OSS) code or talent but scholars have expressed concerns about OSS projects sustainability because of the challenges they face and their high dependency on volunteers' contributions. Acknowledging that (1) challenges that contributors worry about may impact their level of engagement (2) there have been few research on nonpathological worry with non-clinical samples in work-related context as opposed to the pathological and clinical focus (3) calls have been made for further empirical research on equifinality perspective at a micro- and meso-level (or group level) as opposed to organizational level, and from a behavioral perspective. This exploratory research uses factor and cluster analysis to derive empirical worrying profiles and examines profile differences in the relative level of relevant antecedents as well as equifinality in terms of contributors' engagement (hours per week working on OSS projects). Based on an open dataset from a worldwide survey (N = 1024), the study reveals the existence of four dimensions of OSS worry construct and five worrying profiles with marked configurational differences: no major worry (34.70%), major worry on software quality (19.30%), major worry on attraction and retention (18.60%), major worry on entrepreneurial responsibilities (12.40%), and major worry on communications (15%). Among the five profiles, two profiles exhibit equifinality with high (equifinal) engagement level. • Open source project worry construct contains four dimensions. • There are five worrying profiles of open source project contributors. • Different profiles are associated with different levels of contributors engagement. • Two different profiles may lead to equifinal levels of contributors engagement.